(untitled) (Indian Journal of Child Health, 2021)
Objective: The objective of the study was to study the epidemiological and clinical profile of COVID-positive children without pre-existing comorbidities at a dedicated COVID care hospital in the eastern state of Jharkhand. Materials and Methods: This retrospective study was conducted at a COVID hospital of the eastern state of Jharkhand on children up to 18 years of age admitted between May 2020 and October 2020. The case files of all children, with a positive reverse transcription polymerase chain reaction (RTPCR) report for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus, were reviewed, and among them, all children without comorbidities were enrolled and studied. Relevant demographic details, clinical presentation, examination findings, investigations, and treatment received, were collected. Results: Out of 70 children enrolled in the study, 41 were male with a sex ratio of 1.4:1 and a median age (interquartile range) of 14 (8–16.5) years. About 94.2% of children had a history of contact with a positive member from their own family. About 14.2% had a history of travel to an endemic zone. About 34.2% of children were completely asymptomatic and in rest of the children, cough (23.8%) followed by fever (20.0%) was the most predominant complaint. Most of the symptomatic children had mild disease (62.8%). There was no mortality and all children were successfully discharged. The mean duration of disease (based on RTPCR status) was significantly lower in children up to 12 years of age in comparison to those older than 12 years. Conclusion: Family transmission is the major source of SARS-CoV-2 infection in children. Children can also serve as potential source of spread of infection in community. Age was the most important determinant of early recovery in pediatric population without comorbidities.